The Flexible Electrochromic Device That Turns Blue Under Both Positive and Negative Application Voltages - Jin, Shiqi; Zhang, Xuejian; Guo, Xu; Zhu, Mimi; Liu, Ping (Frontiers in Nanotechnology, 2022)
Using the photocurable electrolyte solution containing viologen derivative 1,1′-bis- (4-vinylbenzyl)-4,4′-bipyridinium dihexafluorophosphate (EV2+•2PF6−) and its composite of EV2+•2PF6− and triphenylamine derivative N,N′-di(4-((3-(triethoxysilyl)-propyl)imino)methyl)phenyl-N,N′-diphenyl-4,4′-biphenyldiamine (TPB-PSSO) as the electrochromic active layer, respectively, the flexible electrochromic devices (FECDs) were prepared by photocurable technology. The device structure was PET-ITO/photocurable electrolyte solution/PET-ITO. The electrochromic properties of FECDs were investigated. The results show that the FECDs can all undergo a reversible color change, especially the PET-ITO/photocurable electrolyte solution-composite/PET-ITO can undergo polychromatic transition. The FECD based on EV2+•2PF6− can reversibly change between colorless and deep blue, and the FECD based on the composite of TPB-PSSO-EV2+•2PF6− can reversibly change between black blue, light yellow, and sky blue.